Resistência de milho crioulo a lagarta-do-cartucho em Sistema de Semi-campo - Neves, Rodrigo Valdez Brito (2022)
The occurrence of pests is one of the biggest problems in the sweet corn crop. The main pests include the fall armyworm (Spodoptera frugiperda). Larvae attack corn plants throughout the crop cycle, causing economic losses. The objective of this work was to analyze the intensity of damage caused by S. frugiperda larvae in cultivars of Creole maize in a greenhouse. The experiments were carried out on the campus of UFMT – Federal University of Mato Grosso Araguaia, located at 15°52'23.2” S, 52°18'50.9” W, which has a humid tropical climate with an annual average of temperature, humidity relative and precipitation of 26ºC, 80% and 1503 mm. The experimental design used was the planting in randomized blocks of 5 cultivars and 5 replications in a greenhouse, in 2L polymer pots, using neutral substrate, fertilizing according to the needs of the crop. Planting was carried out on October 27, 2021. Ten days after emergence, S. frugiperda was inoculated in cultures with caterpillars for 3 days per plant to ensure the presence of caterpillars in the corn and the absence of infestation by other insects. Although the average damage score was higher than the recommended control level after the first evaluation, it was observed that there are very promising varieties that can be used in programs that use the landrace varieties under study for sustainable agriculture, such as Pipoca Roxa and Pipoca Preta. Work in field systems is recommended to better understand the use of these varieties. Creole corn cultivars called Pipoca Preta and Palha roxa have the potential for lower susceptibility to S. frugiperda damage. The injuries caused by S. frugiperda are increasing over time.